Presence and potential distribution of malaria‑infected New World primates of Costa Rica - Dolz, Gaby (2022)
Background: In South and Central America, Plasmodium malariae/Plasmodium brasilianum, Plasmodium vivax, Plasmodium simium, and Plasmodium falciparum has been reported in New World primates (NWP). Specifically in Costa Rica, the presence of monkeys positive to P. malariae/P brasilianum has been identified in both captivity and in the wild. The aim of the present study was to determine the presence of P. brasilianum, P. falciparum, and P. vivax, and the potential distribution of these parasites-infecting NWP from Costa Rica. Methods: The locations with PCR (Polymerase Chain Reaction) positive results and bioclimatic predictors were used to construct ecological niche models based on a modelling environment that uses the Maxent algorithm, named kuenm, capable to manage diverse settings to better estimate the potential distributions and uncertainty indices of the potential distribution. Results: PCR analysis for the Plasmodium presence was conducted in 384 samples of four primates (Howler monkey [n = 130], White-face monkey [n = 132], Squirrel monkey [n = 50], and red spider monkey [n = 72]), from across Costa Rica. Three Plasmodium species were detected in all primate species (P. falciparum, P. malariae/P. brasilianum, and P. vivax). Overall, the infection prevalence was 8.9%, but each Plasmodium species ranged 2.1–3.4%. The niche model approach showed that the Pacific and the Atlantic coastal regions of Costa Rica presented suitable climatic conditions for parasite infections. However, the central pacific coast has a more trustable prediction for malaria in primates. Conclusions: The results indicate that the regions with higher suitability for Plasmodium transmission in NWP coincide with regions where most human cases have been reported. These regions were also previously identified as areas with high suitability for vector species, suggesting that enzootic and epizootic cycles occur.